Immediate effects of Graston Technique on hamstring muscle extensibility and pain intensity in patients with nonspecific low back pain - Won, Young Sik; Cho, Hwi-Young; Jung, Jin-Hwa; Moon, Jong Hoon (Journal of Physical Therapy Science, 2017)
[Purpose] The purpose of this study was to analyze the effect of Graston Technique on hamstring extensibility and pain intensity in patients with nonspecific low back pain. [Subjects and Methods] Twenty-four patients with nonspecific low back pain (27–46 years of age) enrolled in the study. All participants were randomly assigned to one of two groups: Graston technique group (n=12) and a static stretching group (n=12). The Graston Technique was used on the hamstring muscles of the experimental group, while the static stretching group performed static stretching. Hamstring extensibility was recorded using the sit and reach test, and a visual analog scale was used to measure pain intensity. [Results] Both groups showed a significant improvement after intervention. In comparison to the static stretching group, the Graston technique group had significantly more improvement in hamstring extensibility. [Conclusion] The Graston Technique is a simple and effective intervention in nonspecific low back pain patients to improve hamstring extensibility and lower pain intensity, and it would be beneficial in clinical practice.